Language development and its risk factors on children - Santamaría, Ángela (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The study has analysed the language functioning in relation with risk factors and mediation in children, bearing in mind the biological risk factors (gestational age), children attention capacities and maternal sensibility as mediators. Based on previous research, it was analysed if a higher gestational age is related to a better language at 24 months, having the children attention and maternal sensibility as mediators. The methodological approach is a qualitative literature review with descriptive scope. The error of assuming that children with language or speech development delays, including children from bilingual homes, born later, or with chronic otitis media, will catch up their pairs without intervention was highlighted. In all these cases the importance of monitoring the development by the parents and teachers was highlighted, including a paediatric integral examination, in order to define delays and disorders the diagnostic thresholds should be used, thus, the clinical procedure that allows establish and apply strategies based on management, treatment and therapy, according to individual needs, should be followed.